Ritual effectiveness framework for non-profit organisations (NPOs) / Ruhaya Atan … [et al.] - Atan, Ruhaya; Zainon, Saunah; Yap, Bee Wah; Rahim, Azlina; Yeow, Roland, Theng Nam (Research Management Institute (RMI), 2013)
This study proposes a framework for non-profit organisations (NPOs) ritual effectiveness integrating both the tangible and intangible dimensions: clients’ satisfaction, programmes and service’s efficiency, increase in clients, programmes and service’s quality, and programmes and service’s effectiveness. With strong impetus for accountability, the movement toward performance or effectiveness evaluation has gained momentum particularly in non-profits as this sector is becoming increasingly important as a result of its continuous growth. There are 44,936 registered non-profit organisations with the Registry of Societies (ROS) as at March 2009. However, for-profit performance indicators are inappropriate to be applied in non-profits, given their multiple services and programs, lack of bottom line motive, and the difficulty of measuring outputs.The motivation behind this study is to establish the performance framework for NPOs effectiveness with multiple dimensions. Ritual effectiveness uses both tangible and intangibles effectiveness dimensions in evaluating NPOs effectiveness. This study will provide the framework for performance (effectiveness) of NPOs in Malaysia with outside (external) bench marking as a foundation. This framework will assist the regulatory body, the Registry of Society (ROS) to regulate NPOs in Malaysia to provide better performance reporting. This is important since effectiveness measures have an impact on the allocation of resources, thus assist the Welfare Department to allocate the resources to those high-performace or NPOs.